Animal performance, carcass characteristics and beef quality of steers fed with a whole oat or maize grain-based diet - Villaverde, María Sol (2023)
Aim of the study: We evaluated the use of oat grain as an alternative source of energy to maize grain in high energy finishing diets. Maize crop production in arid and semi-arid areas is poor or non-existent. Thus, small grains such as oats have become an alternative in high energy rations due to their versatility and ease of cultivation.Area of study: Semiarid region of Buenos Aires province, Argentina.Material and methods: Sixteen Angus steers were randomly assigned to two dietary treatments based on whole oats grain (OD) or whole maize grain (MD) for 61 days. Diets were formulated iso-nitrogenous and iso-energetic. Animal performance, carcass attributes and beef quality traits were evaluated. Longissimus thoracis steaks were wet-aged at 4°C for either 4 or 14 days.Main results:Similar results were found between OD and MD for the variables of performance, carcass evaluation and water retention in fresh meat. No interactions between diet and ageing period were found for any of the variables evaluated. The MD beef was lighter and had a redder appearance than the OD beef. The 4 days-aged beef showed higher values of L*, a* and b* and was more saturated than the 14 days-aged beef. However, the perception of beef colour by the human eye, evaluated through the CIEDE2000 metric, showed no differences among diets and ageing periods.Research highlights: Oat grain could be used in replacement of maize grain as an energy source in fattening rations of beef cattle, obtaining similar animal performance and meat quality.